Ag–Ni nanoparticles supported on multiwalled carbon nanotubes as a cathode electrocatalyst for direct borohydride–hydrogen peroxide fuel cells. (1st May 2022) - Yu, Su Sang; Lee, Tae Hoon; Oh, Taek Hyun
Highlights: Ag–Ni electrocatalyst supported on MWCNTs was investigated for DBHPFCs. Catalyst characteristics were determined through various techniques. The catalyst's performance was evaluated under fuel cell operating conditions. Ag41 Ni59 /MWCNTs showed good catalytic activity and stable performance. Ag41 Ni59 /MWCNTs can be used as a new type of cathode electrocatalyst for DBHPFCs. Abstract: In this study, an Ag–Ni electrocatalyst supported on multiwalled carbon nanotubes (MWCNTs) was investigated to develop a new type of cathode electrocatalyst for direct borohydride–hydrogen peroxide fuel cells (DBHPFCs). Monometallic electrocatalysts consisting of Au, Ag, or Ni have previously demonstrated relatively high catalytic activity and selectivity. The characteristics of each catalyst (Au/MWCNTs, Ag/MWCNTs, and Ni/MWCNTs) were determined through various techniques, such as scanning electron microscopy, energy dispersive X-ray spectroscopy, transmission electron microscopy, and X-ray diffraction; additionally, their performance was evaluated using a fuel cell test. Based on the results, Ag and Ni were selected to construct a bimetallic electrocatalyst, owing to their relatively superior catalytic selectivity at high current densities. Ag–Ni/MWCNT catalysts with various atomic percentage ratios were prepared, and their characteristics were investigated. Among the bimetallic electrocatalysts, Ag41 Ni59 /MWCNTs exhibited the highest maximum power density. Furthermore, Ag41 Ni59 /MWCNTs exhibited good catalytic selectivity even at high operating temperatures. The prepared Ag–Ni bimetallic electrocatalyst has moderate catalytic activity and selectivity and is more cost effective than Au and Ag catalysts; therefore, it can be used as a new type of cathode electrocatalyst for DBHPFCs.